Household Production and Time Allocation Behaviour to Climate Change of Nepal - Bista, Raghu Bir (Journal of Population and Development, 2021)
This study investigates empirically how forest resources production and time allocation’s behavior links with climate change issues by using a household survey in a mid-hill village of Nepal. We use Cobb Douglas’s production function theory to develop a household production function econometric model. We use two-character households: unemployed and forest-dependent population for observation of time allocation behavior for household production. In addition, we use poverty and illiteracy of household characters for understanding its effect on household decision behavior and production behavior. In outcomes of the study, household production behavior of rural people results in higher dependency on forest biomass and its consequence climate change cause issue.